Contribution of women’s preference to the overuse of caesarean sections: A propensity score matching analysis based on a multi-country cross-sectional survey, as part of the QUALI-DEC project - Camille Etcheverry; Ana Pilar Betrán; Marion Ravit; Charles Kaboré; Pisake Lumbiganon; Guillermo Carroli; Quoc Nhu Hung Mac; Celina Gialdini; Alexandre Dumont (PLoS ONE, 2025)
Introduction Maternal request for caesarean section has often been cited to justify the increasing caesarean section rates worldwide. However, we lack evidence on the impact of women’s preference for caesarean section on this dramatic tendency. Given the need to develop appropriate strategies to reduce unnecessary caesarean section, the objective of this study was to assess the association between women’s preference for caesarean section and its actual use, and to estimate the proportion of caesarean section associated with women’s preference for caesarean section in Argentina, Burkina Faso, Thailand and Viet Nam. Methods A cross-sectional hospital-based survey among postpartum women was conducted in 32 hospitals (8 per country) between 2020 and 2022. We selected women with no potential medical indication for caesarean section among a random sample of women who delivered in participating facilities during the data collection period. We chose a propensity score matching approach, to compare the probability of giving birth by caesarean section between women who, late in pregnancy, preferred caesarean section and those who preferred vaginal birth. Results A total of 1,827 low-risk women were included, of whom 10.4% preferred a caesarean section and the average caesarean section rate was 24.5%. The results show that, on average, preference for caesarean section increased the probability of having a caesarean section by 32% (CI 95% [0.23–0.41]; p < 0.001). The relative risk was estimated at 2.69 (CI 95%: 2.43; 2.95) and the fraction of caesarean section associated with women’s preference was estimated at 15% (CI 95%: 12.9% − 16.9%). Conclusion Although women’s preference plays a role in the use of caesarean section in the participating hospitals, it likely accounts for only a small proportion of the caesarean section performed, highlighting the need for multidimensional, context-specific strategies to reduce unnecessary caesarean sections (providing women with evidence-based information, improving clinicians’ adherence to guidelines and shared decision-making, addressing systemic factors…).